THE INFLUENCE OF SERVICE QUALITY ON USER SATISFACTION THROUGH OFFICIAL CREDIBILITY AT SUKABUMI PUBLIC LIBRARY - DEDI MULYADI; IKE RACHMAWATI; SUGIHARTTO (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2023)
Ideally, services in the library can be more attractive, friendly, fast, and accurate. This means that the orientation of library services must be based on user needs, anticipation of developments in information technology and friendly service, in other words, placing users as one of the factors. However, the results of a community satisfaction survey conducted in February 2023, the Sukabumi Regency library obtained a satisfaction index below 28 or was in the Unsatisfactory category. This study aims to analyze the effect of service quality and staff credibility on user satisfaction at the Sukabumi District Public Library. Descriptive method with quantitative approach and verification method used in this research. The research population is the average number of users from January to March 2022, with a total population of 650 users. The research sample of 388 users was selected using simple random sampling technique. The data obtained from the samples were analyzed using inferential partial least squares (PLS) analysis using the smartPLS application. The results of the data analysis show that service quality has a significant and positive influence on the credibility of officers. In addition, the credibility of officers also has a significant and positive influence on user satisfaction. Furthermore, service quality also has a significant and positive influence on user satisfaction through the credibility of officers as mediators. These findings indicate that improving and improving the quality of services provided by librarians can increase the user's perception of the credibility of the officers. In addition, the high credibility of officers can also increase user satisfaction with the services and facilities provided by the Sukabumi District Public Library. Therefore, it is suggested that libraries increase training and skills development for officers in providing the information needed by users and pay attention to other factors such as the strategic location of the library. This research contributes to the understanding of the factors that influence user satisfaction at the Sukabumi District Public Library. The results of this study can be used as a basis for improving service quality, officer credibility, and user satisfaction in an effort to improve library services as a whole.